The obstacles to the application of e-learning in private schools in the Bani Ubaid District in Irbid in light of the Corona pandemic from the teachers' viewpoint - Abu Irsheed, Abd Alrahman Muhammad (Journal of Educational and Psychological Sciences, 2021)
This study aimed to identify the obstacles to the application of e-learning in private schools in the Bani Ubaid District in Irbid in light of the Corona pandemic from the teachers' viewpoint. The descriptive and analytical approach was adopted by applying a questionnaire, which in its final form consists of (25) items, to a sample of (489) private school teachers in Bani Ubaid District in Irbid.The findings revealed that the teachers' views of the obstacles to e-learning in private schools in the Bani Ubaid District are high with a mean of (3.60), and a percentage (72%). Where the third field “Obstacles related to students, ” it ranked first with a mean of (3.80), a percentage (76%) and a (high) degree. The first field “infrastructure- obstacles "ranked last with a mean (3.35) a (high) degree, and by a percentage (67%). The results also showed that there are statistically significant differences between the responses of the participants on all areas of obstacles to e-learning in private schools in Bani Ubaid District from the teachers' viewpoint attributed to the gender variable, and the differences were in favor of males. The results also showed that there are differences attributable to the experience variable between the category (more than 10 years) and the categories (less than five years) and (5-10 years), and the results are in favor of categories (less than five years) and (5-10 years).
Keywords: E-learning; Corona virus; Barriers; Private school; Bani Ubaid District; teachers